Preferential binding of p53 tumor suppressor to p21 promoter sites that contain inverted repeats capable of forming cruciform structure - Coufal, Jan; Jagelská, Eva B; Liao, Jack C C; Brázda, Václav (Biochemical and biophysical research communications, 2013)
p53 Is one of the most critical proteins involved in protecting organisms from malignancies and its gene is frequently mutated in these diseases. p53 Functions as a transcription factor and its role in the cell is mediated by sequence-specific DNA binding. Although the genome contains many p53-binding sequences, the p53 protein binds only a subset of these sequences with high affinity. One likely mechanism of how p53 binds DNA effectively underlies its ability to recognize selective local DNA structure. We analyzed the possibility of cruciform structure formation within different regions of the p21 gene promoter. p53 protein remarkably activates the transcription of p21 gene after genotoxic treatment. In silico analysis showed that p21 gene promoter contains numerous p53 target sequences, some of which have inverted repeats capable of forming cruciform structures. Using chromatin immunoprecipitation, we demonstrated that p53 protein binds preferentially to sequences that not only contain inverted repeats but also have the ability to create local cruciform structures. Gel retardation assay also revealed strong preference of the p53 protein for response element in superhelical state, with cruciform structure in the DNA sequence. Taken together, our results suggest that p53 response element's potential for cruciform structure formation could be an additional determinant in p53 DNA-binding machinery.
Keywords: Protein Binding; DNA, Cruciform; sekvence nukleotidů; Cell Line, Tumor; křížová struktura DNA; western blotting; Protein–DNA binding; Computer Simulation; obrácené repetice; Cruciform; Fluorouracil; promotorové oblasti (genetika); nádorový supresorový protein p53; Response Elements; Mutagens; p53; inhibitor p21 cyklin-dependentní kinasy; vazba proteinů; Blotting, Western; mutageny; lidé; fluoruracil; Inverted Repeat Sequences; Humans; responzivní elementy; Promoter Regions, Genetic; chromatinová imunoprecipitace; počítačová simulace; Base Sequence; nádorové buněčné linie; Cyclin-Dependent Kinase Inhibitor p21; Tumor Suppressor Protein p53; Chromatin Immunoprecipitation